Cognitive Aging - Fernandes, Myra (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Given the global demographic shift towards an aging population, there is a pressing need to understand how aging affects cognition. This collection of articles, from across the globe, represents some of the diverse aspects of cognitive aging. These articles investigate the fundamental processes and mechanisms underlying the neural and cognitive changes associated with normal and pathological aging. They describe the many facets of cognition, memory, language and thinking that are affected by the aging process. The articles will hopefully fascinate readers, and entice them to learn more about how such research is conducted, as well as serving as avenues for exploration to compensate for deficits in cognitive function. The studies are cutting edge and offer insight into the development of the theories that best account for the changes in brain and behaviour that affect us all.